Towards Configurable Integrated Project Support Environment - Chladný, Vladimír; Havlice, Zdeněk; Pločica, Ondrej (Computing and Informatics, 2012)
This article discusses the challenge of the Integrated Project Support Environment development. Such an environment could be successfully applicable to a variety of software development project types. Since there are many software development approaches available it is important to choose and use an appropriate development methodology, methods and tools for a given project. The proposed Integrated Project Support Environment allows developers to configure software technology using formal specification to be used for project development.